Sensory evaluation, physicochemical properties and expected glycaemic index of muffin incorporated with wheat flour and pumpkin (Cucurbita moschata) flour. - Nur Nadia Natasya, Mahammud; Napisah, Hussin; Zarinah, Zakaria (2019)
Background and Aims : This study aims to develop the doughnuts that incorporated with different formulated percentages and types of sweet potato flour. Sweet potato flour (SPF) contains less amount of protein but rich in dietary fiber content and carbohydrate, so a successful combination with wheat flour for doughnut production would be nutritionally advantageous. Materials and Methods : In this experiment, sweet potato flour was incorporated in the formulation wheat flour (ratio of 10%, 30%, and 50%) respectively. These samples were then subjected to sensory evaluation prior to be proceeded with physical and chemical analyses. The physical and chemical analyses were determined using the standard methods. The predicted glycaemic index analysis was also evaluated for the respective formulations. Results : On the basis of sensory evaluation, 30% white SPF doughnut had scored the highest mean for overall acceptability. For the physical analysis, it was found that the volume, specific volume, firmness, and chroma decreased as the percentage of SPF increased. Besides, the lower volume was preferable by the respondents. It was also noted that in term of nutritional value, 30% white SPF doughnuts is the most acceptable as it contains higher fiber as compared to others. However, it contains higher fat percentage which may be caused by the cooking method. Moreover, incorporation of 30% SPF contributes to the lowest GI as it reduced the GI for up to 32% as compared to the control doughnut. Conclusion : In conclusion, it was speculated that SPF is a promising potential resource in alleviating the problem of escalating price of wheat in order to use in bakery products at optimum level of substitution. On top of that, the consumption of food with low glycemic index value is associated with better health outcome. Further analysis on method of cooking, storage, and product developments using SPF should be done in order to optimize the usage of sweet potato and prevent the food wasting.